Analisis Literatur Efektivitas Sistem Manajemen K3 di Perusahaan Kecil dan Menengah (UKM) - Alditia AlfaReza; Susilawati Susilawati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Occupational Health and Safety (K3) is a crucial element in ensuring worker welfare and the smooth running of company operations. Even though SMEs (Small and Medium Enterprises) play an important role in the economy, the work accident rate in this sector is still high compared to large companies. Limited resources and lack of management support are often the main obstacles in implementing an effective K3 management system. Objective: This literature study aims to analyze the effectiveness of the K3 management system in SMEs, identify the challenges faced, and provide recommendations for improving the implementation of K3 in this sector. Methodology: This study uses a literature study approach by collecting and analyzing various academic sources including journal articles, government reports and relevant books. The literature search focused on academic databases such as Google Scholar, ScienceDirect, and ProQuest, using keywords such as "OHS management system", "SME", "OHS effectiveness", and "work safety". Results: Findings show that implementing a comprehensive K3 management system in SMEs can reduce work accidents by up to 25% and increase awareness of the importance of K3. However, challenges such as limited resources, lack of management support, and loose regulations remain major obstacles. This study also found that SMEs that implement good K3 practices tend to have better financial performance. To improve K3 implementation in SMEs, increased access to K3 training and resources, ongoing education campaigns, development of a simple and effective K3 management system, as well as government support in the form of incentives and stricter regulations are needed. Conclusion: Although there are many challenges in implementing the K3 management system in SMEs, with the right approach and adequate support, SMEs can achieve a better level of work safety. This will not only improve worker welfare but also productivity and business sustainability. Keywords: Occupational Health and Safety (K3), Small and Medium Enterprises (UKM), K3 Management System, K3 Effectiveness